Dose down‐titration of biological disease‐modifying antirheumatic drugs in daily clinical practice: Shared decision‐making and patient treatment preferences in Japanese patients with rheumatoid arthritis. (12th September 2019) - Komiya, Takaaki; Takase‐Minegishi, Kaoru; Sakurai, Natsuki; Nagai, Hideto; Hamada, Naoki; Soejima, Yutaro; Sugiyama, Yumiko; Tsuchida, Naomi; Kunishita, Yosuke; Kishimoto, Daiga; Kobayashi, Kouji; Kamiyama, Reikou; et al.
Abstract: Aim: To determine characteristics of rheumatoid arthritis (RA) patients in Japan who received the same biological disease‐modifying antirheumatic drugs (bDMARDs) for at least 6 months and to identify factors associated with successful down‐titration of bDMARDs dependent on shared decision‐making. Methods: We included consecutive RA patients who received the same bDMARD with low disease activity or remission for at least 6 months in our two university hospitals. Patients treated with the bDMARD standard dose were defined as SD, while those treated with bDMARD down‐titration were defined as DT. We retrospectively reviewed clinical charts and compared data between the two groups. Results: Of 288 patients with RA, 204 (70.8%) and 84 (29.2%) continued standard dose treatment and underwent down‐titration treatment, respectively. Sixty‐six of 84 (78.6%) down‐titration‐treated patients continued to show low disease activity or remission, whereas 18 (21.4%) relapsed 18.9 ± 24.4 months after bDMARD down‐titration was started. Univariate predictor analysis showed that the probable factors of down‐titration were no history of bDMARD treatment ( P = .001) and low initial Disease Activity Assessment of 28 joint score ( P = .048). Other clinical characteristics had no significant relationship with successful down‐titration. Conclusions: Thus, bDMARD‐naïve patients and those with low initial disease activity are more likely to agree to attempt down‐titration. However, the timing and method of down‐titration should be made in shared decision‐making between patients and rheumatologists.